A novel method of high impedance fault detection and fault resistance calculation based on damping rate double-ended measurement for distribution network. (March 2022) - Yu, Kun; Yu, Quan; Zeng, Xiangjun; Zeng, Jupeng; Ni, Yanru; Zou, Hao; Liu, Feng
Highlights: A real-time damping rate double-ended measurement technology of the distribution network is invented. A high impedance fault detection method based on the damping rate double-ended measurement before and after the fault is proposed, whose detection range is up to 20kΩ. The high impedance fault detection method is very simple, as the fault occurence can be detected by comparing the damping rate ratio with the ratio threshold intuitively. An accurate fault resistance calculation method is proposed, whose calculation error is less than 0.1% at any fault location. Abstract: To detect high impedance fault (HIF) sensitively and calculate the fault resistance (FR) accurately in neutral point non-effective grounded distribution network, a novel HIF detection and FR calculation method based on damping rate (DR) double-ended measurement is proposed. A zero-sequence current is injected into the secondary side of a voltage transformer (VT) at a specific frequency, and a zero-sequence return voltage is measured in the no-load secondary side of the other VT at the same specific frequency, where two VTs are connected to the neutral point in the distribution network. So the DR of the distribution network is accurately measured according to the zero-sequence loop formed by the two VTs, the damping rate ratio (DRR) of the system is calculated combining with the DR under normal operation of the distribution network. Then it is judged whether the HIF occurs based on the comparison between the DRR and the damping rate ratio threshold (DRRT). Furthermore, FR is accurately calculated based on the DR measured before and after the fault and the imaginary part value of the zero-sequence equivalent grounded admittance. To verify the reliability of the method, a typical 10 kV neutral point non-effectively grounded distribution network simulation model is built in the PSCAD/EMTDC. The simulation results show that the effective HIF detection range is up to 20kΩ, the FR calculation error is less than 0.1%.